Melindungi dan Mengelola Keuangan Keluarga: Edukasi Pinjaman Online dan Manajemen Keuangan untuk Ibu-Ibu Desa Babakan: Protecting and Managing Family Finances: Online Loan and Financial Management Education for Women in Babakan Village - Johan, Irni Rahmayani; Yuliati, Lilik Noor; Simanjuntak, Megawati; Muflikhati, Istiqlaliyah; Pratiwi, Ismayanti (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service program was implemented in Babakan Village, Dramaga District, Bogor Regency, focusing on empowering homemakers through financial management education, awareness of online loan risks, and the development of family economic enterprises. The objectives of this activity were to improve financial literacy, strengthen critical awareness of illegal online loans, and train practical skills to support additional family income. The methods used included interactive lectures, group discussions, demonstrations, and hands-on practice, with evaluation using pre-tests and post-tests. The results of the activity showed a significant increase in participants’ understanding of financial management (p-value = 0.035), online loans (p-value = 0.002), and family economic enterprises (p-value = 0.022). Participants also successfully practiced budgeting, food production (meatballs and sempol), and business break-even analysis. These findings indicate that empowerment programs are effective in improving knowledge and skills, thereby contributing to economic resilience and family welfare in the digital era.